The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s12943-015-0394-1
|View full text |Cite
|
Sign up to set email alerts
|

The chemokine receptor CCR6 facilitates the onset of mammary neoplasia in the MMTV-PyMT mouse model via recruitment of tumor-promoting macrophages

Abstract: BackgroundThe expression of the chemokine receptor CCR6 has been previously correlated with higher grades and stages of breast cancer and decreased relapse-free survival. Also, its cognate chemokine ligand CCL20 has been reported to induce proliferation of cultured human breast epithelial cells.MethodsTo establish if CCR6 plays a functional role in mammary tumorigenesis, a bigenic MMTV-PyMT CCR6-null mouse was generated and mammary tumor development was assessed. Levels of tumor-infiltrating immune cells withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 54 publications
(74 reference statements)
1
45
0
Order By: Relevance
“…+ T EM (31,32), Th-17 cells (33), B cells, immature dendritic cells (DCs) (34), and tumor-promoting macrophages (35). We also observed high CD200 expression levels in the TME (Fig.…”
Section: Tme Shapes the Immune Landscape And Determines The Immune Sumentioning
confidence: 59%
“…+ T EM (31,32), Th-17 cells (33), B cells, immature dendritic cells (DCs) (34), and tumor-promoting macrophages (35). We also observed high CD200 expression levels in the TME (Fig.…”
Section: Tme Shapes the Immune Landscape And Determines The Immune Sumentioning
confidence: 59%
“…The expression of stemness-associated inflammatory cytokines namely; IL-6 and IL-8, and gp130 mRNAs were downregulated by 39%, 38% and 34% in Syndecan-1-silenced SUM149 and by 55%, 61% and 49% in SKBR3 upon Syndecan-1 knockdown, respectively. A relevant clue for regulation of IL-6 is the chemokine CCL20, which induces proliferation of cultured human breast epithelial cells [47] and is involved in IL-6 induction [48]. CCL20 mRNA was downregulated by 40% and 51% in Syndecan-1 knockdown SUM-149 and SKBR3 compared to control cells, respectively, suggesting the existence of a Syndecan-1/CCL20/IL-6 axis.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In a model of breast cancer development related to expression of a polyoma virus gene, tumor macrophages were found to be decreased in tumors that developed in CCR6-deficient mice. 28 Two independent studies utilizing different murine models of atherosclerosis found that atheromas developing in CCR6-deficient mice had decreased infiltrating macrophages. 29,30 Murine monocyte migration to CCL20 in vitro was shown in one of these studies.…”
Section: Discussionmentioning
confidence: 99%